IMPLEMENTATION OF THE DELEGATION OF MEDICAL AUTHORITY TO NURSING PERSONNEL IN THE SPECIAL CARE UNIT AT RSUD dr. M. YUNUS BENGKULU - Eka Purwati; Reny Suryanti; Herlambang (Bengkoelen Justice : Jurnal Ilmu Hukum, 2024)
According to statutory regulations, nursing personnel are healthcare professionals with dual authority: the authority to perform nursing actions and medical procedures. Medical procedures carried out by nurses are based on delegated authority, either in the form of written delegation or a mandate. The objectives of this study are: (1) To identify and analyze the procedures for delegating medical authority to nursing personnel in the Special Care Unit at Local Government General Hospital (Indonesian - RSUD) dr. M. Yunus Bengkulu, and (2) To identify and analyze the legal accountability of the delegation of medical authority to nursing personnel in the Special Care Unit at RSUD dr. M. Yunus Bengkulu. The findings of this study reveal that the implementation of medical authority delegation to nursing personnel at RSUD dr. M. Yunus Bengkulu lacked the establishment of specific types of healthcare services eligible for delegation, whether by mandate or delegation, from medical to nursing personnel. The delegation of medical authority to nursing personnel was recorded in the patient progress notes integrated by the responsible physician. Keywords: Implementation, the delegation of authority, medical actions.